A Systematic Review of Intimate Partner Violence Interventions: State of the Field and Implications for Practitioners. (April 2020) - Trabold, Nicole; McMahon, James; Alsobrooks, Shannon; Whitney, Staci; Mittal, Mona
Intimate partner violence (IPV) victimization is a global public health issue and has serious consequences of women's health. While scholars and researchers have made some progress in addressing IPV and its impact across different levels of care, there is a paucity of intervention research in this area. For example, we know little about which intervention models work best for particular groups of IPV survivors. Previous reviews have concluded there is insufficient evidence to recommend specific treatment options for victims, but they have also been limited in scope of target populations or have employed narrow eligibility criteria. This systematic review examined the efficacy and effectiveness of interventions for victims of IPV related to physical and mental health and revictimization. Three large databases were searched and articles were selected using specified criteria. Fifty-seven articles met inclusion criteria. Results indicate that both empowerment-based advocacy and cognitively focused clinical interventions demonstrate positive outcomes on the vast sequelae of violence in the context of an intimate relationship. The heterogeneity of intervention approaches and frameworks makes comparisons across studies challenging, but this review demonstrates that interventions focused on problem-solving/solution seeking, enhanced choice making and the alteration in distorted self-thinking and perception are promising in facilitating and maintaining positive physical and mental health changes for women who experience violence.